2015
DOI: 10.1111/1540-6229.12078
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of LEED Neighborhood Certification on Condo Prices

Abstract: The U.S. Green Building Council offers LEED certification for existing and new neighborhood developments that meet sustainable urban development standards. Features of sustainable urban development have been found to positively affect residential sales prices. We investigate whether the intangible labeling effects of LEED neighborhood certification add a premium to the sales prices of LEED and non‐LEED–certified condos. Using a quasi‐experiment, transaction data from Portland, Oregon, and a spatio‐temporal aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 53 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…This latter aspect is especially relevant for the most exclusive homes because owning such a home could entail psychosocial rewards in their market niche. This kind of impact, however, has not been always find, as in the study by Freybote, Sun and Yang [70], where the intangible labelling effects of LEED neighborhood certification do not lead to a market premium (in opposition to the financial benefits of LEED building scheme, which effectively add a premium to condominium sales prices).…”
Section: The Configuration Of Real Estate Pricesmentioning
confidence: 93%
“…This latter aspect is especially relevant for the most exclusive homes because owning such a home could entail psychosocial rewards in their market niche. This kind of impact, however, has not been always find, as in the study by Freybote, Sun and Yang [70], where the intangible labelling effects of LEED neighborhood certification do not lead to a market premium (in opposition to the financial benefits of LEED building scheme, which effectively add a premium to condominium sales prices).…”
Section: The Configuration Of Real Estate Pricesmentioning
confidence: 93%
“…See http://www.everbluetraining.com/blog/cities-requiring-or-supportingleed-2015-edition. 5 It is also possible for an entire neighborhood to become LEED certified, although Freybote Sun and Yang (2015) found no effect from that on condos in their study of Portland, Oregon. seven topic areas.…”
Section: Introductionmentioning
confidence: 97%
“…It is also possible for an entire neighborhood to become LEED certified, although Freybote Sun and Yang () found no effect from that on condos in their study of Portland, Oregon.…”
mentioning
confidence: 93%
“…Nyikos et al (2012) 33 analysed cost premiums associated with sustainable facility design. Freybote et al (2015) 34 assessed the impact of LEED neighborhood certification on condo prices. Kats et al (2003) 35 found that productivity and health benefits accounted for about 70 and 82% of the respective Net Present Value (NPV) when classifying LEED certification into two groups such as Certified/Silver and Gold/Platinum.…”
Section: Project Cost Performancementioning
confidence: 99%